2009
DOI: 10.1097/pcc.0b013e318194800b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pediatric donation after cardiac death program

Abstract: Although a small percentage of dying patients are eligible for and will undergo DCD, such a program can markedly increase the number of organ donors at a children's hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The only study thus far that determined a PICU DCDD consent rate found it to be 53% at 1 center. 17 We found a wide range of consent rates for donation activity in our region. These rates varied from 38% (DCDD consent rate at regional PICUs) to 68% (consent rate for donation after brain death in our PICU).…”
Section: Discussionmentioning
confidence: 75%
“…The only study thus far that determined a PICU DCDD consent rate found it to be 53% at 1 center. 17 We found a wide range of consent rates for donation activity in our region. These rates varied from 38% (DCDD consent rate at regional PICUs) to 68% (consent rate for donation after brain death in our PICU).…”
Section: Discussionmentioning
confidence: 75%
“…15 More recent studies suggest that for both pediatric and adult recipients, graft and patient survival for DCDD kidney and liver transplants is equivalent to DNDD organs. 23,24,[43][44][45][46] Perhaps as DCDD becomes a more common practice, children will directly benefit from organs recovered by this method of donation.…”
Section: Figurementioning
confidence: 99%
“…22 Conversely, the development of a DCDD protocol at a single pediatric transplant center increased donor rates by .50%. 23 In addition, recent data suggest that longterm recipient and graft survival for both pediatric kidney and liver transplants with the use of DCDD donors may be equivalent to DNDD organs. 24,25 Pediatric DCDD donors are an important component to increasing the donor pool, but it is unclear how these organs are being used on a national level.…”
mentioning
confidence: 99%
“…Recent estimates suggest that DCD could increase the supply of transplantable organs by 20%. 6 A number of subsequent reports and consensus statements have addressed points of controversy, such as the waiting period before the declaration of death and the use of premortem interventions to improve graft function. [7][8][9][10] More recent pediatric studies reporting similar graft survival in kidneys and livers from donors declared dead according to neurologic and cardiovascular criteria have further increased interest in DCD.…”
Section: Introductionmentioning
confidence: 99%